Prospectives of T-cells genetic programming in adoptive immunotherapy of malignancies - O. L. Morozova; V. V. Yakovlev; N. A. Sushentsev (Сеченовский вестник)
The article reviews the literature on adoptive T-cell therapy of malignancies. Adoptive T-cell transfer allows treatment of metastatic disease on the late stages of certain tumors. The method has a number of advantages before traditional antitumor therapy. The special attention is paid to the possibility of adoptive cells genetic programming, which increases the treatment eﬀectiveness and safety in cancer patients. The article also discusses the method introduction into clinical practice.